A relação entre a confiança e as avaliações online: uma análise da autenticidade das avaliações e os impactos nas decisões de compras de jovens de 18 a 29 anos - Souza, Dryelly Andrade de (Brasil, 2024)
Online reviews, also known as e-WOM (electronic Word-of-Mouth), are communication tools that enable consumers to connect on a single platform to share their experiences and opinions about products or services. This study aimed to explore the relationship between trust in online reviews and the purchasing decisions of young people aged 18 to 29. The research employed a quantitative methodology, using questionnaires distributed to a non-probabilistic sample of online shoppers, totaling 135 valid respondents. The results indicated that participants value online reviews as an essential factor in their purchasing decisions, with particular emphasis on reviews featuring videos, photos, or specific details, which were considered crucial for the perception of authenticity. The identified influencing factors showed that, in addition to third-party online reviews on social media, consumers also prioritize recommendations from family members or close friends, especially for high-value products. The study concludes that e-commerce platforms play a critical role in enhancing consumer trust. Therefore, online sellers should pay close attention to reviews and feedback to positively influence consumers' purchase intentions.